1978
DOI: 10.1042/bj1690449b
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and enzymic studies on the characterization of intermediates during the removal of the 14α-methyl group in cholesterol biosynthesis. The use of 32-functionalized lanostane derivatives

Abstract: By using cell-free preparations of rat liver it was shown that the removal of the 14alpha-methyl group (C-32) of steroids containing either a delta7(8) or a delta8(9) double bond is attended exclusively by the formation of the corresponding 7,14- and 8,14-dienes respectively (structures of types III and VIII). Cumulative evidence from a variety of experimental approaches had led to the deduction that delta8(14)-steroids are not involved as intermediates on the major pathway of cholesterol biosynthesis. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…3) (Aparicio et al 2000;Brautaset et al 2000;Gil and Campelo 2002;Carmody et al 2005). This three-step oxidation process has a strong precedent in the CYP51-catalysed oxidative demethylation of sterols (Akhtar et al 1978;Lepesheva and Waterman 2007). Other members of the CYP105 family catalyse simpler hydroxylation reactions in streptomycete polyketide biosynthesis (Fig.…”
Section: Cyp105s In the Biosynthetic Pathways Of Specialized Metabolitesmentioning
confidence: 99%
“…3) (Aparicio et al 2000;Brautaset et al 2000;Gil and Campelo 2002;Carmody et al 2005). This three-step oxidation process has a strong precedent in the CYP51-catalysed oxidative demethylation of sterols (Akhtar et al 1978;Lepesheva and Waterman 2007). Other members of the CYP105 family catalyse simpler hydroxylation reactions in streptomycete polyketide biosynthesis (Fig.…”
Section: Cyp105s In the Biosynthetic Pathways Of Specialized Metabolitesmentioning
confidence: 99%
“…Sterol 14α-demethylation, a general feature of sterol biosynthetic pathways in eukaryotes, has been known and studied for more than three decades [57-60]. At the dawn of the new millennium, the orthologous nature of the first prokaryotic CYP51-like gene in Mtb was confirmed phylogenetically [61] and biochemically [62, 63].…”
Section: Structural and Biochemical Analysis Of Individual Enzymesmentioning
confidence: 99%
“…These are followed by a mechanistically enigmatic third step that removes the carboxaldehyde as formate with concomitant loss of the 14α-hydrogen. Biochemical experiments utilizing isotopically labeled substrates have concluded that the ferric peroxo intermediate mediates the third step, but the precise mechanism remains elusive [26]. To catalyze these two mechanistically distinct reactions, the enzyme must switch between the effective use of Compound I and peroxo intermediates.…”
Section: Introductionmentioning
confidence: 99%